Screening of probiotic Lactobacilli with potential anti-allergic activity based on hyaluronidase inhibition and degranulation of RBL-2H3 cells in vitro. (April 2021) - Lei, Wenping; Liu, Chengguo; Pan, Lina; Peng, Can; Wang, Jiaqi; Zhou, Hui
Abstract: In the present study, the probiotic potential of lactic acid bacteria (LAB) isolated from different dairy sources were evaluated, and probiotics with anti-allergic activity were further screened based on the hyaluronidase inhibition assay and the degranulation of RBL-2H3 cells in vitro . As a result, Out of 20 strains, 15 LAB exhibited desirable probiotic properties and safety in vitro . Considering the suppressive activities on hyaluronidase and β-hexosaminidase release in degranulation-induced RBL-2H3 cells, strains LZ077E, LZ183E, and LZ260E exhibited potential probiotic properties that could be useful for alleviating allergic diseases. To evaluate the reliability of this result, the efficacy of these three strains on the expression of some cytokines and proteins in the signal pathway related to the FcεRI receptor on the RBL-2H3 cell surface were analyzed. The results show three strains exhibited remarkable downregulation of histamine and cytokines TNF-α and IL-4. Similarly, immunoblot analysis revealed that the probiotics also significantly decreased the phosphorylation of Lyn and Syk in RBL-2H3 cells. Our preliminary results may provide some scientific support for the use of probiotics for the treatment of allergic and inflammatory diseases, as well as the rapid screening of anti-allergic active probiotics in vitro . Highlights: A method for rapid screening of anti-allergic probiotics has been established. On this basis, 3 strains with potential anti-allergic activity were screened. Part of the cellular action mechanism of probiotics against allergies was revealed.